Kritik Arsitektur Dalam Cerpen Berjudul “Gubuk Syukur” Karya Maemunah - Granita Hanifah; Yosepha Lilin Rosari Kristi; Eva Dwi Kurniawan (STIKes Ibnu Sina Ajibarang, 2024)
The aim of this research is to determine the differences in the use of materials and spatial layouts used in the past and today. spatial color and spatial arrangement in the short story entitled Gubuk Syukur by Maemunah. Where the owner renovates a house that was previously made of wooden walls into a brick wall house with the spatial arrangement that the homeowner wants. The techniques used in the research when collecting data were heirloom, listening and note-taking techniques. The source of data in this research was the short story Gubuk Syukur. The results of this research show the form of descriptive criticism found in the short story Gubuk Syukur by Maemunah, which in this research uses 3 methods of criticism, namely static criticism, dynamic criticism and process criticism.